Feasibility of smartphone diaries and personal dosimeters to quantitatively study exposure to ultraviolet radiation in a small national sample. Issue 5 (27th April 2015) - Køster, Brian; Søndergaard, Jens; Nielsen, Jesper B.; Allen, Martin; Bjerregaard, Mette; Olsen, Anja; Bentzen, Joan
Summary Background In 2007, a national skin cancer prevention campaign was launched to reduce the UV exposure of the Danish population. To improve campaign evaluation a questionnaire validation using UV‐dosimeters was initiated. Aim To show the feasibility of dosimeters for national representative studies and of smartphones as a data collection tool. Materials and Methods Participants were sent a dosimeter which they wore for 7 days, received a short diary questionnaire by text message each day and subsequently a longer questionnaire. Correlation between responses from questionnaire, smartphone diaries and dosimeters were examined. Results This study shows a 99.5% return rate (n = 205) of the dosimeters by ordinary mail and high response‐rates for a smartphone questionnaire dairy. Correlation coefficients for outdoor‐time reported through smartphones and dosimeters as average by week 0.62 (0.39–0.77), P < 0.001 (n = 40). Correlation coefficient for outdoor time estimated by questionnaire and dosimeters were 0.42 (0.11–0.64), P = 0.008. The subjective perception of the weather was the only covariate significantly influencing questionnaire estimates of actual outdoor exposure. We showed that dosimeter studies are feasible in national settings and that smartphones are a useful tool for monitoring and collecting UV behavior data. Conclusion We found diary data reported on a daily basis through smartphones more strongly associated with actual outdoor time than questionnaire data. Our results demonstrate tools and possible considerations for executing a UV behavior questionnaire validation.